CONSTRUCTION OF GROUT CURTAIN IN KARSTIC ENVIRONMENT CASE STUDY: SALMAN FARSI DAM - Fazeli M.A. (My University, 2007)
Salman Farsi is an arch-gravity dam. It is 125 m high and located on the Ghareh-Agaj River in Fars province, south of Iran. From the geological and hydrogeological point of view, this dam is one of the most complicated sites in Iran. Existence of 40 springs at the river level (including hot springs), and many faults and crushed zones are part of these complications. The dam site is famous for its numerous big caverns. Main characteristics of the rock mass are: (1) low permeable limestone of moderate to high strength, (2) high karstification generally localized around intersection of faults or discontinuities. The main purpose of grout curtains is to change the hydrogeological characteristics (reducing the permeability) of the rock mass. Constructing a grout curtain in a karstic environment with a high random distribution of karst features contains some uncertainties and surprises cannot be excluded. During the excavation of grouting galleries, some big caverns at both abutments were discovered. The volume of the biggest one (Golshan’s Cave) exceeds 150,000 m3. A large-scale underground geotechnical treatment is needed to improve the water tightness of the dam site.
Keywords: GROUTING; CURTAIN; GALLERY; DAM CONSTRUCTION; IRAN